2021
DOI: 10.1002/slct.202101798
|View full text |Cite
|
Sign up to set email alerts
|

Silica Supported Synthesis and Quorum Quenching Ability of Isoxazolones Against Both Gram Positive and Gram Negative Bacterial Pathogens

Abstract: Isoxazolones are synthesised using easily available, economical and reusable silica (TLC grade) catalyst. High yields are obtained in aqueous reaction system with substrate tolerance without affecting the yield. This multigram scale, purification free method exhibits prospects for a large scale use in future. These compounds were screened for their potential application as quorum quenchers in pathogenic bacteria. The prepared compounds were analysed for quorum quenching (QQ) activity on Gram negative bioreport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…This antimicrobial activity observed in A. leptinellae E138 filtrates and extracts may be attributed to the secondary metabolites produced by the endophyte, which could possess biocontrol properties. Several studies have already demonstrated this ability of endophytes to produce antimicrobial compounds that effectively inhibit the growth of bacterial pathogens [62,63] or disrupt bacterial communication mechanisms [63][64][65]. This is in clear agreement with the compounds tentatively identified by mass spectrometry in the methanolic fungal extract of A. leptinellae E138: altechromone A, maculosin, ciclo(L-Phe-L-Pro), and phomopsinone A.…”
Section: Discussionsupporting
confidence: 79%
“…This antimicrobial activity observed in A. leptinellae E138 filtrates and extracts may be attributed to the secondary metabolites produced by the endophyte, which could possess biocontrol properties. Several studies have already demonstrated this ability of endophytes to produce antimicrobial compounds that effectively inhibit the growth of bacterial pathogens [62,63] or disrupt bacterial communication mechanisms [63][64][65]. This is in clear agreement with the compounds tentatively identified by mass spectrometry in the methanolic fungal extract of A. leptinellae E138: altechromone A, maculosin, ciclo(L-Phe-L-Pro), and phomopsinone A.…”
Section: Discussionsupporting
confidence: 79%
“…Many drugs containing isoxazole structure have been used in clinic, such as oxacillin, cloxacillin and dichloropenicillin, which are all effective penicillin antibiotics and can be used for bacterial infection [13] . Especially, recent studies have found that substituted isoxazolone has good resistance to some bacteria like Gram negative bacteria, Gram positive bacteria and mycobacterium tuberculosis [14,15] . Thus, the synthesis of isoxazolone derivatives is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Especially, recent studies have found that substituted isoxazolone has good resistance to some bacteria like Gram negative bacteria, Gram positive bacteria and mycobacterium tuberculosis. [14,15] Thus, the synthesis of isoxazolone derivatives is of great importance. At present, some methods were found to synthesize substituted isoxazole-5(4H)-ones such as cyclization of o-propionyl oximes [16] and one-pot three-component reaction of ethyl acetoacetate, hydroxylamine hydrochloride and aromatic aldehydes.…”
Section: Introductionmentioning
confidence: 99%